MWCNT-Supported PVP-Capped Pd Nanoparticles as Efficient Catalysts for the Dehydrogenation of Formic Acid - Ortega-Murcia, Alejandro; Navlani-García, Miriam; Morallón, Emilia; Cazorla-Amorós, Diego (Frontiers in Chemistry, 2020)
Various carbon materials were used as support of polyvinylpyrrolidone (PVP)-capped Pd nanoparticles for the synthesis of catalysts for the production of hydrogen from formic acid dehydrogenation reaction. Among investigated, MWCNT-supported catalysts were the most promising, with a TOF of 1430 h-1 at 80 ºC. The presence of PVP was shown to play a positive role by increasing the hydrophilicity of the materials and enhancing the interface contact between the reactant molecules and the catalytic active sites.